Adopting al-Hikr long term lease financing for Waqf and state lands in Malaysia to provide affordable public housing - Abdullah, Adam; Meera, Ahamed Kameel Mydin (IIUM Press, 2018)
This concept paper provides a practical, policy solution to deliver affordable public housing. By evaluating price-to-income ratios, it analyzes to what extent housing has become seriously unaffordable in Malaysia. We discuss how the federal government, state governments, state Islamic religious councils (SIRCs) as well as pension and investment institutions can participate, by examining affordable public housing based on an Ottoman long-term lease structure (al-Hikr) and subsequently adopted in the development of waqf land in Singapore and Malaysia. In Singapore, the Housing Development Board adopted the 99-year leasehold (al-Hikr) concept and now houses over 80% of its citizens into low-cost state-built housing. Accordingly, this study adopts case study, library research, documentary analysis and descriptive statistics relating to housing affordability and construction costs, to provide an Islamic social finance solution by adopting al-Hikr for waqf and state lands in Malaysia, to deliver affordable public housing to the bottom 40% (B40) of households by median income.